Quinazolin-4(3H)-ones and 5,6-Dihydropyrimidin-4(3H)-ones from β-Aminoamides and Orthoesters - Joshua T. Gavin (Molecules, 2018)
Quinazolin-4(3H)-ones have been prepared in one step from 2-aminobenzamides and orthoesters in the presence of acetic acid. Simple 2-aminobenzamides were easily converted to the heterocycles by refluxing in absolute ethanol with 1.5 equivalents of the orthoester and 2 equivalents of acetic acid for 12⁻24 h. Ring-substituted and hindered 2-aminobenzamides as well as cases incorporating an additional basic nitrogen required pressure tube conditions with 3 equivalents each of the orthoester and acetic acid in ethanol at 110 °C for 12⁻72 h. The reaction was tolerant towards functionality on the benzamide and a range of structures was accessible. Workup involved removal of the solvent under vacuum and either recrystallization from ethanol or trituration with ether-pentane. Several 5,6-dihydropyrimidin-4(3H)-ones were also prepared from 3-amino-2,2-dimethylpropionamide. All products were characterized by melting point, FT-IR, 1H-NMR, 13C-NMR, and HRMS.